DEVELOPMENT OF A PERSONALIZED MEAT PRODUCT USING STRUCTURAL-PARAMETRIC MODELING - Andrey B. Lisitsyn; Irina M. Chernukha; Marina A. Nikitina (Теория и практика переработки мяса)
At present, there is no consistent definition of the term «personalized nutrition». The paper presents existing descriptors in this field of food science: precision nutrition, nutrigenomics, nutrigenetics, individual nutrition and so on. It is noted that cardiovascular diseases occupy the first place among noninfectious diseases associated with malnutrition. Optimal nutrition leads to a reduction in the risk of their occurrence. The methodology of structural-parametric modeling, which allows designing personalized optimal human nutrition based on medical indicators, is presented in terms of minimization of the risk function. The algorithm of a substantiated optimal choice of mass fractions of components (ingredients) of the food recipe composition is given. The main descriptors of a food product with the antisclerotic action for its designing using structural-parametric modeling are shown.